Morphogenesis and Morphometry of Alluvial Fans in the High Atlas Morocco: A Geomorphological Model of the Fans of the Wadi Beni Mhammed, Souss Valley - Chakir, Lahoucine; Aït Hssaïne, Ali; Bridgland, David (International Journal of Environment, 2014)
Morphosedimentary study of alluvial fans formed by the Wadi Beni Mhammed, on the southern piedmont of the western High-Atlas, has indicated three main generations of deposits. Their ages range from ancient (Plio-Pleistocene) to Holocene and recent formations. The first generation, comprising small boundary fans, was deposited prior to lateral migration and subsequent entrenchment of the drainage pattern (the combination of the Wadis Aït Mekhlouf and Ida Ou Merouane). The confluence of these powerful streams gave birth to the principal fan that extends to the Souss valley. The third generation of fans was constructed after the incision of the principal fan, by the re-activation of a high secondary fan that was formed from downstream progradation. The morphological characteristics of the fans, such as their area, shape and gradient, are determined from catchment data and, in particular, from the lithology of their provenance areas, which defines the nature of gravel material, sedimentation processes and, finally, the distribtion of constituent materials. Fan shape also depends on the available accommodation space on the piedmont. The Wadi Beni Mhammed fans are elongated, because they are constrained by the mega fans of Wadis Irguitene and Aoukourta. DOI: http://dx.doi.org/10.3126/ije.v3i3.11090 International Journal of Environment Vol.3(3) 2014: 293-311